Imaging flow cytometry as a sensitive tool to detect low‐dose‐induced DNA damage by analyzing 53BP1 and γH2AX foci in human lymphocytes. (4th August 2015) - Durdik, Matus; Kosik, Pavol; Gursky, Jan; Vokalova, Lenka; Markova, Eva; Belyaev, Igor
Abstract: Ionizing radiation induced foci (IRIF) are considered the most sensitive indicator for DNA double‐strand break (DSB) detection. Monitoring DSB induction by low doses of ionizing radiation is important due to the increasing exposure in the general population. γH2AX and 53BP1 are commonly used molecular markers for in situ IRIF assessment. Imaging flow cytometry (IFC) via ImageStream system provides a new opportunity in this field. We analyzed the formation of 53BP1, γH2AX foci and their co‐localization induced by γ‐rays (2, 5, 10, 50, 200 cGy) in human lymphocytes using ImageStream and the automated microscopic system Metafer. We observed very similar sensitivity of both systems for the detection of endogenous and low‐dose‐induced IRIF. Statistically significant induction of γH2AX foci was found at doses of 2 and 10 cGy using ImageStream and Metafer, respectively. Statistically significant induction of 53BP1 foci was evident at doses ≥5 cGy when analyzed by IFC. Analysis of the co‐localizing foci by ImageStream and Metafer showed statistical significance at doses ≥2 cGy, suggesting that foci co‐localization is a sensitive parameter for DSB quantification. Assessment of γH2AX, 53BP1 foci and their co‐localization by Metafer and ImageStream showed similar linear dose responses in the low‐dose range up to 10 cGy, although IFC showed slightly better resolution for IRIF in this dose range. At higher doses, IFC underestimated IRIF numbers. Using the imaging ability of ImageStream, we introduced an optimized assay by gating γH2AX foci positive (with 1 or more γH2AX foci) and negative (cells without foci) cells. This assay resulted in statistically significant IRIF induction at doses ≥ 5cGy and a linear dose response up to 50 cGy. In conclusion, we provide evidence for the use of IFC as an accurate high throughput assay for the prompt detection and enumeration of endogenous and low‐dose induced IRIF. © 2015 International Society for Advancement of Cytometry